Budaya Sikap Tanggung Jawab Siswa di Madrasah Aliyah Negeri Insan Cendekia (MAN IC) Lombok Timur - Hidayati Hidayati (Universitas Islam Negeri (UIN) Mataram, 2023)
This article aims to describe the independence of East Lombok MAN IC students in activities both in the dormitory and at school, this is interesting to study because all these activities foster an attitude of deep responsibility so that students make many achievements in the academic and non-academic fields. The research method uses a descriptive qualitative approach. The informants of this research are the Chairperson of LTPM, Curriculum Waka, Caregivers, and students of MAN IC East Lombok. Data collection techniques use observation, interviews and documentation. While the data analysis technique uses Miles and Hubermans data analysis. The results showed that the attitude of responsibility was shown by students in dormitory activities, both reciting the yellow book, tahfiz Al-Qur'an and practicing speeches carried out independently by fellow students. Likewise in school activities, academically they are disciplined in carrying out learning activities according to the time of entry to completion, discipline in complying with all school rules. In the non-academic field, students participating in competitions inside and outside school are mostly students' own initiatives from seeking information, registering to participating in competitions and practicing together, while the school supports all of these student activities if they require certain training such as the science Olympiad competition. This attitude of responsibility makes MAN IC students independent and accomplished. Keywords: Culture, Attitude, Responsibility Artikel ini bertujuan untuk mendeskripsikan kemandirian siswa MAN IC Lombok Timur dalam kegiatan baik di asrama maupun di sekolah, hal ini menarik untuk diteliti karena semua kegiatan tersebut menumbuhkan sikap tanggung jawab yang mendalam sehingga siswa banyak menorehkan prestasi dalam bidang akademik maupun non akademik. Metode penelitian menggunakan pendekatan kualitaif deskriptif, Informan penelitian ini yaitu Ketua LTPM, Waka kurikulum, Pengasuh, dan siswa MAN IC Lombok Timur, Teknik pengumpulan data menggunakan observasi, wawancara dan dokumentasi. Sedangkan teknik analisis data menggunakan analisis data Miles dan Hubermans. Hasil penelitian menunjukkan bahwa sikap tanggung jawab ditunjukkan siswa dalam kegiatan asrama baik ngaji kitab kuning, tahfiz Al-Qurâ€™an maupun latihan pidato dilakukan secara mandiri sesame siswa. Demikian juga dalam kegiatan sekolah, secara akademik mereka disiplin melakukan aktifitas pembelajaran sesuai dengan waktu masuk sampai selesai, disiplin mematuhi semua tata tertib sekolah. Dalam bidang non akademik siswa mengikuti lomba di dalam maupun luar sekolah sebagian besar merupakan inisatif siswa sendiri dari mencari informasi, mendaftar sampai mengikuti lomba dan berlatih bersama, sedangkan pihak sekolah mensuport dengan baik semua kegiatan siswa tersebut jika memerlukan pelatihan tertentu seperti lomba olimpiade sains. Sikap tanggung jawab ini menjadikan siswa MAN IC yang mandiri dan berprestasi Kata kunci:Â Budaya, Sikap, Tanggung Jawab